Break on through: The role of innate immunity and barrier defence in atopic dermatitis and psoriasis - Hawerkamp, Heike C.; Caoimhe, Fahy; Fallon, Padraic G.; Schwartz, Christian (Skin Health and Disease, 2022)
The human skin can be affected by a multitude of diseases including inflammatory conditions such as atopic dermatitis and psoriasis. Here, we describe how skin barrier integrity and immunity become dysregulated during these two most common inflammatory skin conditions. We summarise recent advances made in the field of the skin innate immune system and its interaction with adaptive immunity. We review gene variants associated with atopic dermatitis and psoriasis that affect innate immune mechanisms and skin barrier integrity. Finally, we discuss how current and future therapies may affect innate immune responses and skin barrier integrity in a generalized or more targeted approach in order to ameliorate disease in patients.<br